C++17 Quick Syntax Reference A Pocket Guide to the Language, APIs and Library - Olsson, Mikael (Apress, 2018)
This quick C++17 guide is a condensed code and syntax reference to the popular programming language, fully updated for C++17. It presents the essential C++ syntax in a well-organized format that can be used as a handy reference. In the C++17 Quick Syntax Reference, you will find short, simple, and focused code examples. This book includes a well laid out table of contents and a comprehensive index allowing for easy review. You won't find any technical jargon, bloated samples, drawn out history lessons, or witty stories in this book. What you will find is a language reference that is concise, to the point and highly accessible. The book is packed with useful information and is a must-have for any C++ programmer. You will: Use template argument deduction for class templates Declare non-type template parameters with auto-folding expressions and auto deduction from braced-init-list Apply lambdas and lambda capture by value Work with inline variables, nested namespaces, structured bindings, and selection statements with initializer Use utf-8 character literals Carry out direct-list initialization of enums Use these new C++17 library features or class templates from std::variant, optional, any, string_view, invoke, apply and more Do splicing for maps and sets, also new to C++17.